2006
DOI: 10.1002/anie.200603517
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Asymmetric Autocatalysis in Organocatalytic Reactions

Abstract: Dedicated to Professor Lutz F. Tietze on the occasion of his 65th birthdayAsymmetric autocatalysis is the process of automultiplication of a chiral compound in which the chiral product acts as a chiral catalyst for its own formation.[1] Such reactions offer striking advantages as the chiral product does not need to be separated from the chiral catalyst and as no other chiral catalyst than the product itself is involved. Several examples are known, all of which involve organometallic reagents and are hence rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 19 publications
4
58
0
Order By: Relevance
“…The CDC reaction may proceed in the absence of pyrrolidine because the N-4-methoxyphenylglycine esters 2 c, 3 k, and 3 m are secondary amines and might perform autocatalysis of the CDC reaction. [14] To gain insight into these CDC reactions, we carried out preliminary studies on the mechanistic pathway. We found that if 2,6-di-tert-butyl-4-methylphenol (BHT), a radical inhibitor, was added to the reaction system with TBHP [Eq.…”
Section: Jin Xie and Zhi-zhen Huang*mentioning
confidence: 99%
“…The CDC reaction may proceed in the absence of pyrrolidine because the N-4-methoxyphenylglycine esters 2 c, 3 k, and 3 m are secondary amines and might perform autocatalysis of the CDC reaction. [14] To gain insight into these CDC reactions, we carried out preliminary studies on the mechanistic pathway. We found that if 2,6-di-tert-butyl-4-methylphenol (BHT), a radical inhibitor, was added to the reaction system with TBHP [Eq.…”
Section: Jin Xie and Zhi-zhen Huang*mentioning
confidence: 99%
“…PMP-protected iminoester could be synthesized in one step and in high yield from ethyl glyoxylate. [41] The resulting products could be deprotected under mild conditions using CAN. Moreover, the PMP-protected iminoester are more stable than their corresponding imines such as tosylimine.…”
Section: Resultsmentioning
confidence: 99%
“…Fully organic examples of asymmetric autocatalysis [51], which, similar to the Soai reaction, can also show the behavior of an absolute asymmetric synthesis, were first reported by Mauksch and Tsogoeva in 2007 [52]: an asymmetric Mannich-type product -a functionalized amino acid -was able to replicate itself and with the same absolute configuration (Figure 23.7). DFT (density functional theory) calculations showed that the formation of homochiral product dimers is kinetically preferred with respect to formation of heterochiral dimers in the autocatalytic steps [52].…”
Section: Autocatalytic Enantioselective Reactionsmentioning
confidence: 99%
“…DFT (density functional theory) calculations showed that the formation of homochiral product dimers is kinetically preferred with respect to formation of heterochiral dimers in the autocatalytic steps [52]. …”
Section: Autocatalytic Enantioselective Reactionsmentioning
confidence: 99%